Conclusions on the Way Forward for Evaluation in Difficult Times - Richard Boyle; Drew Koleros; Rob D. van den Berg (Journal of MultiDisciplinary Evaluation)
Background: The evaluation profession faces unprecedented challenges in an era of global uncertainty, with shifting political climates, rising populism, and complex societal problems requiring innovative evaluation approaches. Moments like these are opportune times to harvest learnings from the past to inform current and future evaluation practice.